The Effect of Antioxidantson Electrolytes in Vancomycin- Streptozotocin InducedDiabetes Kidney Disease inRabbits. - Raghda Tuama; Falah Shari; Usama Ramadhan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Diabetes mellitus is a metabolic disease that is characterized by relative or absolute insulin deficiency,diabetic kidney disease (DKD) seems to be one of the most common complications of diabetes mellitus.Diabetic kidney disease was known as diabetic nephropathy (DN) and is the single strongest predictor ofmortality in patients with diabetes. Forty male and female rabbits weighing 1000-1300 mg were dividedrandomly into five groups. Diabetes mellitus was induced in the overnight fasted rabbits by a single IPinjection ofStreptozotocin in dose of 50 mg/kg. Then animals were started of antioxidant treatment, bloodsampling were taken each 2 weak, the laboratory analysis which includes blood sugar, and serum electrolytes(potassium, sodium, and chloride).The various antioxidants were used in different combination in treated 1group (quercetin15 mg/kg and L-carnitine15 mg/kg) and treated 2 group (quercetin15 mg/kg, L-carnitine15mg/kg, Thioctic acid 20mg/kg, Vitamin C 15mg/kg) orally.There was a non-significant decrease in serumglucose level in treated 1 group andtreated 2 group (which treated with different combination of antioxidants)compared with diabetic control group and significant increase in serum (potassium, and chloride) but nonsignificantincrease in serum sodium in treated groups compared with diabetic control group.The role ofantioxidants as adjuvant therapy to decrease and prevent diabetic kidney disease through the scavengingeffect to reactive oxygen species produced by diabetic kidney tissues.